THE FRAME OF SHARIA ECONOMIC ON PAYLATER PAYMENT SYSTEM - Rif’atul Muzayanah Al-Mahbubah; Ana Nurwakhidah (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2021)
This study aims to investigate the payment system mechanism in Paylater in Shopee e-commerce, as well as to find out the contract used in the payment system and to review the system in the frame of Islamic law. This research was prompted upon a loan system namely Paylater provided by Shopee e-commerce, one of the biggest markerplaces in Indonesia, which offers loans with installment system. The method used in this research was a field research method. In this study, the researchers gathered data by themselves. The data was obtained from the application regarding public knowledge of Paylater Shoppe payments. The results showed that the payment system mechanism is relatively easy to follow since the application provides simple and practical instructions. Meanwhile, the contract used in Paylater payments is bai 'as-salam, where there are still similarities and differences that still need to be studied. In conclusion, in a review of Islamic law the Paylater system is categorized as usury and gharar